2011
DOI: 10.1111/j.1399-0004.2010.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoautosomal inheritance of Léri-Weill syndrome: what does it mean?

Abstract: The short stature homeobox (SHOX) gene is located in the pseudoautosomal region 1 of both sex chromosomes. Haploinsufficiency of SHOX leads to different phenotypes ranging from isolated short stature to Léri-Weill syndrome characterized by short stature, mesomelia and Madelung deformity. We describe a family with a SHOX deletion originally located on the Y chromosome and transmitted from father to daughter by crossover during meiosis. The male index patient presented with short stature, mesomelia and mild Made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
4
1
1
Order By: Relevance
“…1992 ), 2) the estimated genetic size of PAR1 in normal males is ∼50 cM ( Flaquer et al. 2009 ; Evers et al. 2011 ; Otto et al.…”
Section: Resultscontrasting
confidence: 61%
“…1992 ), 2) the estimated genetic size of PAR1 in normal males is ∼50 cM ( Flaquer et al. 2009 ; Evers et al. 2011 ; Otto et al.…”
Section: Resultscontrasting
confidence: 61%
“…However, most reports discussed recombination events in the PAR1 in the context of a Y-located SHOX deletion transmitted from father to daughter or included pedigrees that did not differentiate between Y- and X- chromosomal SHOX mutations [5-8]. Indeed, to our knowledge, the transfer of an originally X-located SHOX deletion to the Y chromosome after transmission from father to son has only been documented by FISH in two patients in the literature to date, and not in an apparently phenotypically normal male child [9,10].…”
Section: Case Presentationmentioning
confidence: 99%
“…Recent studies have shown that deletions in the downstream enhancer region of SHOX, and (less frequently) in the upstream enhancer region (SHOX enhancer deletions (SEDs)), can result in a clinical picture similar to that of SHI (5,6,7,8,9,10). In about two-thirds of cases LWD is caused by intragenic point mutations or deletions of the complete coding sequence of SHOX, and in one-third of cases by deletions in the enhancer sequences in the 3 0 -or 5 0 -flanking region of SHOX, leaving the gene itself intact (11).…”
Section: Introductionmentioning
confidence: 99%